FORMATION OF KNOWLEDGE AND SKILLS IN DESIGNING SPATIAL IMAGINATION IN STUDENTS IN ENGINEERING GRAPHICS CLASSES (Web of Teachers: Inderscience Research, 2025)
To consider methods and techniques aimed at improving spatial thinking in the process of teaching engineering graphics